Optimización basada en colonia de hormigas para resolver problemas asignación de horarios en la Universidad Técnica Estatal de Quevedo - Oñate Espinoza, John Alexander (2016)
The constant advance of the technology and the increase in the demand of automation of the present time in the different fields, in the education, health and economy, conventional software does not satisfy the requirements of optimization and quickness in the planning of tasks, in This case the generation of class schedules, requires planning with constant changes which entails an investment of time and effort. This research project presents the description and development of the web application, which applies the ant colony optimization metaheuristics, for the generation of schedules of the Quevedo State Technical University of the Faculty of Engineering Sciences, with the purpose Of decreasing teacher and student dissatisfaction during the time management process, it should be emphasized that every application does not deliver 100% optimal results, but rather an approximation to the ideal, due to the complex model due to the number of restrictions that must be met and satisfy. Through the process of generation of time four modules are implemented, the Administration and the Load of Data allow management of the information and in turn to assign to the teachers a certain parallel, Generation of Time in the module can generate the schedules and Schedule Reconstruction are used to modify the schedule generated by parallel. For the present case study was used information from the Faculty of Engineering Sciences belonging to the State Technical University of Quevedo; In the tests carried out satisfactory results were obtained in which 25 parallels belonged to the cycle 1, 5 mesh of the following careers: systems, electrical, mechanical, telematics and industrial safety, 86 teachers with their respective positions, this information Was obtained from the distributive provided by Engineer Efrain Diaz, one of those in charge of performing distributions at Quevedo State Technical University.